Advances in chimeric antigen receptor-natural killer cell therapy: from mechanisms and preclinical studies to clinical application - Ren, Tianyuan; Wang, Fengjiang; Liu, Xuan; Guo, Jun; Xie, Sitan (Frontiers in Oncology, 2026)
Chimeric antigen receptor T-cell therapy (CAR-T) has revolutionized cancer treatment, yet its application remains limited by high costs, safety concerns, and challenges in solid tumors. Natural killer (NK) cells offer a promising alternative due to their innate tumor-killing capacity, diverse cell sources, lower risk of graft-versus-host disease and cytokine release syndrome, and potential for “off-the-shelf” production. This review synthesizes recent advances in CAR-NK, focusing on NK-specific CAR engineering strategies, preclinical models across hematological and solid malignancies, and the latest clinical trials up to 2025. We highlight distinctive CAR-NK optimization approaches, such as integration of Fc-binding domains, cytokine armoring, and strategies to overcome tumor microenvironment mediated resistance, that distinguish CAR-NK from CAR-T platforms. Key challenges, including insufficient in vitro expansion, manufacturing scalability barriers, in vivo persistence, and the immunosuppressive effects of the tumor microenvironments (TME), as well as their corresponding potential technical solutions, are critically analyzed. By integrating the latest translational insights, this review aims to provide a forward-looking perspective on CAR-NK as a next-generation immunotherapeutic modality.